Decision Making When Implementing Supervision of Learning Implementation at Deli Murni Bandar Baru Private High School - Yohanes Kefi; Saut Purba; Yuni Selia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The purpose of the study was to describe the implementation of learning supervision in terms of decision-making at Deli Murni Bandar Baru private high school and the problems encountered in the implementation of learning supervision related to decision-making at Deli Murni Bandar Baru private high school. This study uses a descriptive qualitative approach. The research subject was the school principal, while the informants were two teachers. Data collection techniques are observations, interviews, and documentation. The results of the study showed that: The implementation of learning supervision by the principal to the teacher was carried out at the beginning of the first semester using an assessment rubric, including teacher effective assessment. Teacher's professional attitude. Assessment of teacher teaching skills. The learning supervision document is in the form of a file/questionnaire to assess teacher performance. The problems encountered in the implementation of learning supervision at Deli Murni Bandar Baru Private High School are the lack of supervision coaching time available by the school principal for teachers, lack of facilities that support the implementation of learning supervision, such as available learning media, lack of readiness of teachers to take part in supervising school learning.